Biomass power generation development in Thailand - Chai, Chompoo Inwai; Chow, Chompoo Inwai; Leelajindakrairerk, Monthon; Banjongjit, Sulee; Fuangfoo, Pradit; Lee, Wei Jen (My University, 2009)
The emerging global warming crisis results from carbon dioxide emission has drawn an attention about renewable energy all over the world. Thailand is a developing country located at the heart of Southeast Asia with almost 70 million of population as of 2008. The ESI structure under the government of Thailand has been managed by the Electricity Generating Authority of Thailand (EGAT), Metropolitan Electricity Authority (MEA), and Provincial Electricity Authority (PEA) for almost 50 years. According to the Power Development Plan (PDP 2007), during the year 2007-2021, the government of Thailand plan to have the most economic power generation resources yet reliable and least environmental impact. To achieve those goals, there are three strategic plans which are to import power from neighboring country, to promote the renewable power generation from the public power companies, and to have a variety on power generations resources. This paper discusses the biomass power generation development in Thailand. System overview processes and biomass fuel consumed for the electricity production process are also presented. ©2009 IEEE.
Keywords: Biomass power generation; Fixed adder; Power tariff; Very small power producer (VSPP)